2013
DOI: 10.1111/jopy.12039
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Active Assortment in Spousal Similarity

Abstract: Previous research has established the existence of active assortment, that is, a preference for similarity in a potential mate. Few studies, however, have directly related mate preferences to dyadic similarity by examining them in the same participants. We collected both similarity and mate preference data in two studies: undergraduate students (N = 519) and newlyweds (N = 335). In both studies, women placed a higher value on desirable personality characteristics (e.g., higher Conscientiousness and Agreeablene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
49
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 43 publications
(117 reference statements)
7
49
1
Order By: Relevance
“…Lee et al, ; Liu, Ludeke, & Zettler, ), we found robust support for similarity preference for it. At the same time, and relatively consistent with previous work (Figueredo et al, ; Watson et al, ), we did not observe a strong preference concerning different levels in Openness ascribed to one's ideal partner as compared with oneself. We see two potential explanations for this.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Lee et al, ; Liu, Ludeke, & Zettler, ), we found robust support for similarity preference for it. At the same time, and relatively consistent with previous work (Figueredo et al, ; Watson et al, ), we did not observe a strong preference concerning different levels in Openness ascribed to one's ideal partner as compared with oneself. We see two potential explanations for this.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, our results suggest that singles (when asked via questionnaires) tended to exhibit aspirational assortative preference in their ideal partners concerning Honesty–Humility, Emotionality, Extraversion, Agreeableness, and Consciousness. Singles did not indicate a preference for higher nor lower trait levels in Openness in their ideal partners compared with themselves, which both mirrors previous findings in general (Figueredo et al, ; Watson et al, ) and matches its unique status as the only Big Five trait with no connection to relationship satisfaction (Malouff et al, ).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The lacking assortative mating for these three broad personality traits in the current research is in line with other publications (e.g., Botwin et al, 1997;Montoya et al, 2008;Watson, Beer, & McDade-Montez, 2014;Watson et al, 2004). The present findings and other recent findings demonstrating similarity effects for Psychopathy, Machiavellianism (Smith et al, 2014), and antisocial behavior (Krueger, Moffitt, Caspi, Bleske, & Silva, 1998) suggest that assortative mating might be relatively stronger for "dark" traits.…”
Section: Comparison With Broader Personality Traitssupporting
confidence: 92%